Clinical study on 77 cases of sialolithiasis - ISHIHARA, Hiroshi; HANDA, Kimihiko; HONMA, Shouko; WATANABE, Yaeko; NAKAJIMA, Tamio; HAMAMOTO, Yoshioki (Japanese Journal of Oral and Maxillofacial Surgery, 1990)
Clinical results in 76 cases of sialolithiasis of the submandibular gland and a case report of multiple parotid sialoliths are presented. Sialolithiasis of the submandibular gland occurred most frequently in the fourth decade of life. There was no sex prevalence. The submandibular duct was the most common site of involvement (67.2%) and sialoliths were found in two or more of the duct, gland and transitional portion in 9. 2% of the cases. As compared to 24. 9 months in patients with sialoliths in the duct, the period from the onset of symptoms to the initial visit in patients with intraglandular sialoliths was longer (96.7 months). The most common chief complaint was a swelling and/or pain of the submandibular region. In patients with intraductal sialoliths, the main symptoms included swelling and/or pain of the submandibular region or of the mouth floor and they often manifested themselves on eating, whereas sialoliths in the gland and transitional portion were associated less frequently with symptoms of the mouth floor and eating episodes. Sialoliths could not be demonstrated in 9 patients with plain radiographs. Sialoliths were removed by intraoral sialolithotomy in 43 of 51 patients with intraductal sialoliths and 7 of 9 patients with sialoliths in the transitional portion, whereas sialoliths were removed by sialoadenectomy of the submandibulr gland in 8 of 9 patients with intraglandular sialoliths and in 2 patients with sialoliths in the transitional portion. A combination of the two procedures was employed in 5 of 7 patients with sialoliths at more than 2 different sites. Six sialoliths evacuated spontaneously and sialolithotomy was not done in 5 patients because of poor systemic condition, or reluctance to receive a treatment probably due to the absence or disappearance of acute symptoms. Two sialoliths were found in the duct and the gland of parotid with CT.